KESALAHAN PENGGUNAAN BAHASA INDONESIA PADA PAPAN NAMA SEKITAR MEDAN BARU PADANG BULAN - Dita Ananda Br Gurusinga; Tiara Elisabet Siagian; Trisnawati Hutagalung (FKIP, Universitas Palangka Raya, 2023)
Language is a tool in communicating. A signboard is one of the means to expedite business functions which contain information related to the shop. Errors in the use of Indonesian are still common, especially in the writing on the sign. In the Medan Baru Padang Bulan area, errors in the use of spelling and punctuation were the most common errors found on nameplates, while errors in language use of word choice (diction) were minimal. Factors that cause language errors, namely the influence of the language they master first, the lack of understanding of the language users of the language they use, and the teaching of language that is not precise and imperfect. Besides that, mistakes, fatigue, and lack of attention are also factors that cause language errors so that someone forgets the function of spelling, punctuation, and word choice.